Identifying AIM2 Circulating Methylation Levels as a Novel Diagnostic Biomarker for Rheumatoid Arthritis Using Targeted DNA Methylation Sequencing - Zhao, Jianan; He, Binghen; Shan, Yu; Wei, Kai; Jiang, Ping; Shi, Yiming; Chang, Cen; Zheng, Yixin; Zhao, Fuyu; Li, Yunshen; Zheng, Yuejuan; Jin, Yehua; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2026)
IntroductionThis study investigated the association between AIM2 cg11003133 DNA methylation and Rheumatoid Arthritis (RA), evaluating its diagnostic potential for RA and subtypes.MethodsMethylTarget™ sequencing targeted AIM2 cg11003133 (chr1:159076528-159076740) in RA, Ankylosing Spondylitis (AS), Psoriatic Arthritis (PsA), gout, Systemic Lupus Erythematosus (SLE), Dermatomyositis (DM), primary Sjögren's Syndrome (SS), and Healthy Controls (HC) patients. Logistic regression, random forest, and XGBoost models were applied, with Spearman’s correlation used to assess associations.ResultsRA and RF/CCP-positive patients showed significantly higher methylation at cg11003133_79/91 compared to HC and AS (FDR < 0.05), but lower levels compared to DM. Methylation at cg11003133_139 was elevated in RA compared to AS/SS (FDR = 0.04/0.03). Anti-TNF-α non-responders had higher cg11003133_79/91 methylation levels compared to HC/AS non-responders (FDR < 0.05). RF-negative RA patients had higher cg11003133_91 methylation than AS patients who failed anti-TNF-α treatment (FDR < 0.05). Haplotype CCCC correlated positively with CRP (r = 0.14, P = 0.006); TTTT was significantly negatively correlated with erythrocyte sedimentation rate, CRP, and the presence of diabetes (r = -0.18, -0.15, and -0.14; P < 0.001, 0.003, and 0.008, respectively). XGBoost and RF models achieved AUCs of 0.9911 and 0.9975 for RA versus non-RA, and 1 for RF/CCP double-negative versus double-positive RA.DiscussionAIM2 cg11003133 methylation is strongly linked to RA, aligning with its role in inflammasome activation. While promising for diagnostics, larger validation is needed.ConclusionsAIM2 cg11003133 methylation may serve as a diagnostic biomarker for RA and subtypes.
Keywords: diabetes